Evaluation of the use of laparoscopic-guided cholecystocholangiography and liver biopsy in definitive diagnosis of neonatal cholestatic jaundice - Khalid Shreef; Abdullah Alhelal (Wolters Kluwer Medknow Publications, 2016)
Background: Once it is established that a jaundiced infant has direct hyperbilirubinemia, the principal diagnostic concern is to differentiate hepatocellular from obstructive cholestasis. Traditional tests such as ultrasonography, percutaneous liver biopsy and technetium 99 m hepatobiliary iminodiacetic acid (HIDA) scan are often not sufficiently discriminating. Definitive exclusion of biliary atresia (BA) in the infant with cholestatic jaundice usually requires mini-laparotomy and intra-operative cholangiography. This approach has many drawbacks because those sick infants are subjected to a time-consuming procedure with the probability of negative surgical exploration. Aim of the Study: The aim of this study was to determine the feasibility of laparoscopic-guided cholecystocholangiography (LGCC) and its accuracy and safety in the diagnosis of BA and thus preventing unnecessary laparotomy in infants whose cholestasis is caused by diseases other than BA. Patients and Methods: Twelve cholestatic infants with direct hyperbilirubinemia subjected to LGCC (age, 7-98 days; mean, 56 days) after ultrasound scan and (99 mTc) HIDA scan and percutaneous liver biopsy failed to provide the definitive diagnosis. Results: One patient had completely absent gall bladder (GB) so the laparoscopic procedure was terminated and laparotomy was done (Kasai operation). Four patients had small size GB; they underwent LGCC that showed patent common bile duct with atresia of common hepatic duct, so laparotomy and Kasai operation was performed. Seven patients had well-developed GB, LGCC revealed patent biliary tree, so laparoscopic liver biopsies were taken for histopathology. Five of those patients had neonatal hepatitis, and two had cholestasis as a complication of prolonged TPN. No perioperative complications or mortalities were recorded. Conclusion: When the diagnosis neonatal cholestasis remains elusive after traditional investigations, LGCC is an accurate and simple method for differentiating BA from hepatocellular causes.